To find the terms of the sequence described by the rule \( A(n) = -3 + (n-1)(6) \), we will substitute the values of \( n \) for the third, fourth, and eleventh terms.
-
Finding the third term \( A(3) \): \[ A(3) = -3 + (3-1)(6) \] \[ = -3 + (2)(6) \] \[ = -3 + 12 \] \[ = 9 \]
-
Finding the fourth term \( A(4) \): \[ A(4) = -3 + (4-1)(6) \] \[ = -3 + (3)(6) \] \[ = -3 + 18 \] \[ = 15 \]
-
Finding the eleventh term \( A(11) \): \[ A(11) = -3 + (11-1)(6) \] \[ = -3 + (10)(6) \] \[ = -3 + 60 \] \[ = 57 \]
Summary of Terms
- \( A(3) = 9 \)
- \( A(4) = 15 \)
- \( A(11) = 57 \)
Thus, the third term is \( 9 \), the fourth term is \( 15 \), and the eleventh term is \( 57 \).